Study of The Potential of Palm Oil Empty Core Fiber As Composite Materials for Ship Hull - Harefa, Daniel Kurniawan (Indonesian Journal of Maritime Technology, 2023)
Palm oil is the largest commodity in Indonesia. Pprocessing of oil palm, leaving 20% to 23% empty palm fruit bunches (EFB). Oil palm empty fruit bunches (EFB) is a collection of fiber left behind after separating the fruit from fresh fruit bunches that have been sterilized. Some researchers use natural fibers as an alternative for making composites. This study aims 1. To determine the tensile strength of the alternative material of palm empty fruit bunch fiber. 2. To determine the buckling or bending strength of the alternative fiber material for empty palm oil bunches. The method used is the tensile and bending test method in the process of mixing the fiber material of empty palm oil bunches in the manufacture of composites. The test results obtained were compared with the BKI composite standard. The volume fraction used in this study was 30% polyester resin and 70% EFB fiber, 40% polyester resin and 60% EFB fiber and 50% polyester resin and 50% EFB fiber with NaOH alkaline treatment for 2 hours. The average tensile stress values obtained for each fraction were 27.372 MPa, 24.168 MPa and 25.875 MPa respectively. The values for the bending stress of each fraction are 144.836 Mpa, 149.059 Mpa and 164.682 Mpa respectively.